Pelatihan First Aid Bagi Masyarakat Tenant Bandar Udara Husein Sastranegara Bandung - Kurniawan, Wahyu; Santosa, Asri; Machmiyana, Ichyu; Gunawan, Fandhy; Soebagio, Agoes; Yusmana, Wawan (Politeknik Penerbangan Indonesia Curug, 2022)
First Aid is an effort to help and provide temporary care for accident victims before receiving more perfect help from a doctor or health worker. Community participation in helping victims before receiving treatment by health workers is very important to minimize the risk of a more severe condition. Tenants at the airport are places that are very prone to emergency conditions caused by dense activities with many visitors. To anticipate this problem, we as lecturers at the Indonesia Curug Aviation Polytechnic propose a PKM activity with the title: First Aid Training for the Husein Sastranegara Airport Tenant Community - Bandung. It is hoped that participating in training can add to the knowledge and insights of the tenants of Husein Sastranegara Airport - Bandung who participate in this activity regarding first aid and can take first aid measures if needed. It is hoped that after participating in the first aid training, they can add to the knowledge and insight of the tenants of Husein Sastranegara Airport - Bandung who take part in this activity regarding first aid and can take first aid measures if needed.